Effect of Placental Cryoextract on Morphofunctional State of Kidneys in Heymann Nephritis - Vaskovich, Aleksey M.; Kondakov, Igor I.; Repin, Nikolay V. (Problems of Cryobiology and Cryomedicine, 2016)
Probl Cryobiol Cryomed 2016; 26(2):175.